Game Card Quartets for Increasing Numeracy Ability of Adding 1-10 for Intellectual Disability Students - Anton Cahyo Yuwhono; Wiwik Dwi Hastuti (Department of Special Education, 2019)
This research was conducted with the aim to determine the effect of quartet card games towards the numeracy ability of adding 1-10 for intellectual disability students in the grade III SDLB. This study used an experimental research model pre-post design. The conclusion of this quasi-time-series experimental method is that the quartet card game can improve the numeracy ability of adding 1-10 for students with intellectual disability in the grade III SDLB.